News in Brief - Maruenda, Helena (2014)
- Peru needs more scientists and researchers to be competitive in today's world.- PUCP upgrades its NMR to a potent 500 MHz instrument. This is still the only NMR for research that exists in Peru.- The Chemistry Festival in Lima.- The Chemistry Degree from PUCP receives an international accreditation diploma.